2020
DOI: 10.1177/1357633x20942045
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth during the coronavirus disease 2019 pandemic: Rapid expansion of telehealth outpatient use during a pandemic is possible if the programme is previously established

Abstract: Introduction The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted the health-care system both in Australia and internationally, and has rapidly transformed the delivery of health care in hospitals and the community. Implementation of social isolation and distancing measures to stop the spread of the disease and to reduce potential harm to patients has necessitated the use of alternate models of health-care delivery. Changes that would normally take months or years have occurred within da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 31 publications
5
49
0
1
Order By: Relevance
“…The mean daily number of telehealth appointments rose from 8.30 in February to 195.5 in April in a tertiary hospital in Australia. 46 A comparison of more than 8,000 e-visits and office visits found virtual encounters cheaper and popular with no compromise on quality. 1 Consistent with previous studies, [47][48][49][50][51][52] we observed overall high patient satisfaction with virtual encounters across various disease types such as epilepsy, dermatology, diabetes, cancer, IBD, and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mean daily number of telehealth appointments rose from 8.30 in February to 195.5 in April in a tertiary hospital in Australia. 46 A comparison of more than 8,000 e-visits and office visits found virtual encounters cheaper and popular with no compromise on quality. 1 Consistent with previous studies, [47][48][49][50][51][52] we observed overall high patient satisfaction with virtual encounters across various disease types such as epilepsy, dermatology, diabetes, cancer, IBD, and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are particularly relevant given that the COVID-19 pandemic has increased the deployment of telehealth across the country. [14][15][16] In addition, we also conducted secondary descriptive analyses and found differences based on the modality in which telehealth was deployed. One health system that utilized multiple different modalities found that for conditions such as eye infections, skin conditions, and allergies, telephone was equally as effective at achieving resolution as video.…”
Section: Discussionmentioning
confidence: 99%
“…The recent COVID-19 pandemic has laid testament to the feasibility as well as the rapid and successful uptake of telemedicine. 77 The need for an increased usage of eHealth care and telemedicine is warranted to provide multidisciplinary team access as well as follow-up care to patients not only from rural areas, but to those who are unable to visit hospitals thereby reducing unnecessary travel and discomfort. A suggestion was made to increase the number of trained pancreatic cancer specialists to work at centres in urban and regional Australia earmarked to provide comprehensive oncology care.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have discussed this complex issue in further detail in a recent manuscript 76 highlighting the need for multiple actions ranging from the administrative level to tackle problems associated with access to medical care and increase in resource allocation, to revisiting the model of centralization, as we understand it, to equip centres in metropolitan as well as regional areas to comprehensively manage pancreatic cancer by boosting surgical and medical oncology services as well as palliative care. The recent COVID‐19 pandemic has laid testament to the feasibility as well as the rapid and successful uptake of telemedicine 77 . The need for an increased usage of eHealth care and telemedicine is warranted to provide multidisciplinary team access as well as follow‐up care to patients not only from rural areas, but to those who are unable to visit hospitals thereby reducing unnecessary travel and discomfort.…”
Section: Discussionmentioning
confidence: 99%